Stimuli-Responsive Drug Delivery Systems for Enhanced Melanoma Immunotherapy - Zhang G; Zhang X; Dong Q; Kong S; Chen L; Zhang X; Gao J; Zhang J; Ding B (Drug Design, Development and Therapy)
Guoqing Zhang,1,2 Xiaojuan Zhang,1 Qiuxiang Dong,3 Shuaizhi Kong,2 Lihua Chen,2 Xiaoqing Zhang,1 Jianqing Gao,4 Jie Zhang,1 Baoyue Ding1 1Department of Pharmaceutics, Jiaxing Key Laboratory for Photonanomedicine and Experimental Therapeutics, College of Medicine, Jiaxing University, Jiaxing, 314001, People’s Republic of China; 2College of Pharmaceutical Science, Zhejiang University of Technology, Hangzhou, 310014, People’s Republic of China; 3Department of Chemical Drug Inspection, Baoding Institute for Food and Drug Control, Baoding, 071000, People’s Republic of China; 4College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, 310058, People’s Republic of ChinaCorrespondence: Baoyue Ding, Department of Pharmaceutics, Jiaxing Key Laboratory for Photonanomedicine and Experimental Therapeutics, College of Medicine, Jiaxing University, No. 118 Jiahang Road, Jiaxing, Zhejiang, 314001, People’s Republic of China, Tel/Fax +86-0573-83643808, Email lena_310@163.com Jie Zhang, Department of Pharmaceutics, Jiaxing Key Laboratory for Photonanomedicine and Experimental Therapeutics, College of Medicine, Jiaxing University, No. 118 Jiahang Road, Jiaxing, Zhejiang, 314001, People’s Republic of China, Tel/Fax +86-0573-83643808, Email zhangjiepharm@zjxu.edu.cnAbstract: Melanoma results in the formation of malignant tumors and is the deadliest form of skin cancer with high mortality rate. Immunotherapy for melanoma has made great breakthroughs in recent decades. However, low patient response rates and side effects due to the immunosuppressive tumor microenvironment (iTME) and tumor heterogeneity limit the clinical application of melanoma immunotherapy. The tumor microenvironment (TME) exhibits characteristics such as weak acidity, hypoxia, and aberrantly expressed proteases. By exploiting these features, researchers have developed stimuli-responsive drug delivery systems (DDSs) to enhance antitumor immune responses in melanoma patients. This review aims to clarify how stimuli-responsive DDSs enhance melanoma immunotherapy and guide their use as therapeutic agents. We summarize the categorization and design of these DDSs, analyze their immune-enhancing pathways, and discuss current challenges and future prospects in the field.Keywords: malignant melanoma, stimuli-responsive, nanoparticles, immunotherapy